2007
DOI: 10.1097/01.blo.0000238784.98606.d4
|View full text |Cite
|
Sign up to set email alerts
|

Argon Beam Coagulation as an Adjuvant for Local Control of Giant Cell Tumor

Abstract: The argon beam coagulator is gaining popularity as an adjuvant therapy for treatment of giant cell tumors of bone. However, the effectiveness and functional implications of this treatment have not been assessed. To determine whether the argon beam coagulator could be a viable adjuvant treatment option, we examined the recurrence rate and functional outcome of patients with giant cell tumors who were treated with the argon beam coagulator, as an adjuvant to curettage and cementation. Thirty-seven patients who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…Previous studies reported a higher local recurrence rate in patients with GCTB and a pathological fracture treated with curettage . Other studies did not confirm the previous reports .…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous studies reported a higher local recurrence rate in patients with GCTB and a pathological fracture treated with curettage . Other studies did not confirm the previous reports .…”
Section: Discussionmentioning
confidence: 69%
“…The cavity was then curetted with a high‐speed burr and washed with saline to remove all pathological tissue . Then, in 11 patients, phenol was applied to the tumor cavity with cotton‐tipped swabs followed by washing with alcohol for neutralization while in two patients argon beam coagulator was used as a paintbrush throughout the entire cavity . The tumor cavity was then filled with bone allografts (five patients), cement (five patients), cement and bone allografts (one patient), or hydroxyapatite graft (two patients).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…phenol, alcohol, sterile water, heat, freezing, zinc, and hydrogen peroxide (Nicholson et al 1998, Malawer et al 1999, Trieb et al 2001, Ghert et al 2002, Ward and Li 2002, Haskell et al 2003, Zhen et al 2004. Recently, argon laser therapy has been added to the list (Lewis et al 2007). None of these methods were used extensively in the present series and their indications remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, 3 lesions showed soft tissue masses with extensive edema, which proved to be a prognostic marker of local recurrence [28]. Further, pathological fractures were considered not only a potential marker of aggression [29], but also a prognostic factor for local recurrence [30]. Although the prognostic value of cortical discontinuity and soft tissue mass is still debated, there is broad agreement that soft tissue mass extension definitely influences ideal surgical treatment selection.…”
Section: Discussionmentioning
confidence: 99%